Effects of Diet and Physical Activity on BMI of Medical Students: Cross Sectional Study - Muhammad Razi Ul Islam Hashmi, Shaiza Shoaib, Syeda Saba Sajjad, Ahmed Amer, Shaheer Asrar Minhas, Ahsan Amer, Mahnoor Fatima, Sheikh Ali Ateeq, Tayyaba Shafiq, Shoaib Naiyar Hashmi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Most common method of measuring body fat of a person is through BMI. It is used to define obesity and overweight people across states, cities and, races. Aim: To find the link between healthy nutrition and physical activity with BMI. Study Design: Cross Sectional study. Methodology: Data was collected using convenient sampling. A total of 60 students were selected of which 31 were students of 3rd year and 29 were of 4th year, ageing between 20-24 years. Accurate weight and height of each student were measured to calculate BMI. Cut off points according to WHO were used to define the prevalence of obesity and overweight. The volunteers were asked to answer a questionnaire comprising of 13 questions based upon typical day with regard to sleep, food, education. Data was evaluated by using SPSS version 24. The results were presented as counts (percentage), means and, standard deviation as appropriate. Results: Findings indicated that 3rd year students had a little higher BMI. Most of them slept for less than 5 hours a day whereas almost all 4th year students were having ample amount of sleep. Eating habits of 3rd year MBBS was irregular as compared to 4th year MBBS students. Students of 4th year MBBS were having some kind of physical activity but 3rd year MBBS student had almost no physical activity. Practical Implication: Present study highlighted few important factors that caused high BMI among medical students thus depicting an inverse relationship between BMI and physical activity. Hence, raised the importance of physical activity among medical students in our society. Conclusion: It was concluded that irregular eating habits and lack of time for sleep and physical activity was the most frequently mentioned barriers to healthy eating habits and engaging in regular exercise. Thus routine should be made for regular physical activity in-order to reduce BMI and for improvement in quality of life. Keywords: BMI, Physical Activity, Diet, Relationship, Students and Healthy Life.